Methods for the Development of Reading Culture during the School Life (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the modern world, the ability to read effectively and efficiently is more crucial than ever before. Reading is a fundamental skill that opens up a world of knowledge, information, and entertainment. However, in an era characterized by information overload and digital distractions, fostering a culture of reading has become increasingly challenging. This article explores various methods that can be employed to promote and develop a strong reading culture in the modern world.